Újabb magyarországi jogtanuló a 16. századi strasbourgi Academián (Kiegészítés az eddigi peregrinusnévsorhoz) - P. Szabó, Béla (Gerundium, 2018)
Yet Another Law Student from Hungary at the Strasbourg Academy (an Additon to the hitherto known list of Peregrine students). In the second part of the 16th century the municipal school of the Alsatian metropolis Strasbourg, was one of the popular destinations among wanderer, peregrine students from Hungary. In this school – beyond the liberal arts (artes liberales) – students could attend lectures on theology, medicine and law. Since the contemporaneous parish register of the school was lost it is hitherto unclear how many Hungarian students studied here until the foundation of the university in 1621. From the study offered here one can obtain information pertaining to a young student who has not been counted as a student in Strasbourg so far and who was originally from the Sips (Zips) region, and studied law on the evidence of two, hitherto unknown disputes of his. The paper is completed by an attempt to reconstruct earlier student lists: according to our knowledge it can be attested that Hungarian and Transylvanian students did actually study in Straßsbourg from the middle of the 16th century till 1621.